Effects of different urea-based fertilizers on gaseous and hydrological nitrogen losses from subtropical citrus orchards - Jing Zheng; Hongyu Lin; Xingling Wang; Hongyang Dong; Bowen Zhang; Hui Cheng; Shouzheng Jiang; Ralf Kiese; Klaus Butterbach-Bahl; Minghua Zhou (Agriculture, Ecosystems & Environment, 2026)

Computational, pharmacokinetic and wastewater-based evidence for persistent carbamazepine metabolites and their ecological risks in municipal wastewater treatment plants - Kai He; Jinlong Yuan; Yingchao Lin; Nian Shi; Kexin Tang; Hongyang Wang; Shinya Echigo; Wen Liu (Environmental Pollution, 2026)

Synergistic magneto-aeration photocatalysis over AgI/TiO2/mrGO composite for high-salinity recalcitrant wastewater - Chunxia Zhao; Bingqian Wei; Feng Lin; Hongyang Xue; Yuxin Li; Miaomiao Cheng; Hongjie Wang (Chemical Engineering Journal, 2026)

Ultrahigh-resolution flexible quantum-dot light-emitting diodes via dual assembly and transfer printing - Xin Hu; Yangbin Zhu; Runzhen Sun; Zhen Wang; Jiayu Sun; Qinghong Lin; Yi Jiang; Hongyang Fu; Kejia You; Xuan Guo; Yue Wang; Deli Li; et al. (Chemical Engineering Journal, 2026)

Nanomaterials as plant delivery carriers: transport mechanisms and design principles - Ye Li; Yezhuo Zhang; Zhun Zhang; Xi Zhang; Hongyang Wu; Man Zhang; Zhuo Li; Yinglang Wan; Yujie Fu; Wei Dong; Ruili Li; Jinxing Lin (Science China Life Sciences, 2026)

Colonization of bioelectrochemical system biofilms by low-adhesive denitrifiers: Promotion by electroactive bacteria - Feng Lin; Xin Li; Jianguo Zhang; Wei Guo; Yongze Lu; Guangcan Zhu; Hongyang Wang (Environmental Research, 2026)

Multi-omics profiling complements physicochemical monitoring by revealing functional signatures of dissolved oxygen status in the Xijiang River - Jizhou Cao; Kai He; Xiaohong Chen; Jiabiao Wang; Qidong Yin; Wei Ouyang; Hongyang Wang; Jiachong Lin; Chenguang Fan (Water Research, 2026)

KAR1 Priming Breaks Seed Dormancy by Regulating Antioxidant System and Plant Hormones Under High Temperature in Lettuce Seeds - Hongyang Wang; Fuyuan Chen; Dexin Wang; Jing Leng; Qilin Deng; Xiulan Xu; Yang Xia; Jian Ma; Shuchun Meng; Lin Cheng; Yanhong Qiu; Haijun Zhang (Journal of Plant Growth Regulation, 2026)

Influence of hydro-mechanical parameter coupling on the dynamic behavior of unsaturated railway subgrades - Shumeng Wu; Liqun Zeng; Jing Hu; Zhongfeng Yang; Hongyang Ke; Xin Ding; Zhihang Lin; Xuecheng Bian (Soil Dynamics and Earthquake Engineering, 2026)

Endophyte-engineered plant immunity: A post-GMO strategy for programmable crop defense - Fan Zhang; Jing Zheng; Xinyun Xie; Mengru Tang; Hongyang Li; Linyin Zuo; Lu Zheng; Hao Liu; Junbin Huang; Zhinan Mei; Xiao-Lin Chen (Molecular Plant, 2026)

Simultaneous removal of sulfamerazine and nutrients in wastewater by alternate coupling of photocatalysis and microalgal system: From system construction to multi-interactions and purification effects - Lin-Lan Zhuang; Rui Li; Xiao-Xiong Wang; Yuxin Wu; Yanhui Zhao; Xiaojia Yi; Hongyang Liang; Weiyi Qian; Jian Zhang (Chemical Engineering Journal, 2026)

Load mitigation in floating wind turbines via active tuned mass damper using a physics-informed neural network based controller - Jianing Fu; Shuyue Lin; Hongyang Dong; Xiaowei Zhao (Ocean Engineering, 2026)

Optimizing synergistic microalgae cultivation and photocatalysis processes for antibiotic and nutrient removal in wastewater - Lin-Lan Zhuang; Hongyang Liang; Weiyi Qian; Zhen Hu; Xiao-Xiong Wang; Jian Zhang (Bioresource Technology, 2026)

Color-categorized microplastics in rivers and lakes: Global distribution, driving mechanisms, and ecological risks unveiled by interpretable machine learning - Tianqi Jiang; Guangshuo Chai; Qiong Guo; Haoran Peng; Yuexia Guo; Xiaohui Zhang; Yan Lin; Hongyang Cui; Xiaoyu Cui; Yindong Tong (Journal of Environmental Chemical Engineering, 2025)

Robust CoNi-ZIF@PAN nanofiber membranes with prewetting-induced reversible wettability for switchable emulsion separation and catalytic dye degradation - Yiyi Lin; Huaqiang He; Thabang Mokoba; Hongyang Chen; Shaojun Yuan (Journal of Environmental Chemical Engineering, 2025)

Massive carbon inputs from fish farming reduce carbon sequestration capacity in a macroalgae mariculture area - Wei Yang; Yingxu Wu; Yanmei Liu; Peiqiang Zhuang; Chenglong Li; Jianhang Zhang; Yingfeng Chen; Yanpei Zhuang; Hongyang Lin; Huaji Qiu; Youjun Huang; Weijie Qiu; et al. (Marine Environmental Research, 2025)

Development of cyclic double virtual phase model for advanced packed bed solar-driven thermo-chemical reactor - Hongyang Zuo; Qingyang Zhang; Kuo Zeng; Meng Lin; Ange Nzihou; Haiping Yang; Hanping Chen (Chemical Engineering Journal, 2025)

Proton exchange membranes with oriented ion channels for enhanced conductivity - Bingru Lu; Hongyang Ma; Zhanfeng Deng; Jun Lin; Zhongrui Lu; Tianxu Jin; Shaoxiong Zhai; Jiahua Li; Peng Sheng; Qing Ye; Hui Jin (Chemical Engineering Journal, 2025)

Synthesis of sodium silicate-activated metakaolin geopolymer microspheres (SS@MGMs) for efficient F− removal from acidic wastewater - Lin Shao; Min Yi; Hongyang Wei; Riwen Ji; Liu He; Yuxiao Jiang; Kaituo Wang (Applied Clay Science, 2025)

Diapycnal fluxes of nutrients in the North Pacific Subtropical Gyre - Chuanjun Du; Minhan Dai; Zhiyu Liu; Zhendong Hu; Jin-Yu Terence Yang; Kuanbo Zhou; Hongyang Lin; Zhongwei Yuan; Lifang Wang; Tao Huang; Liguo Guo; Zhe Wang; et al. (Global and Planetary Change, 2025)

Research on Calibration Methods and Experiments for Six-Component Force Sensors - Hongyang Zhao; Bowen Zhao; Xu Liang; Qianbin Lin (Journal of Marine Science and Engineering, 2025)
The measurement accuracy of six-component force sensors is crucial for reliable hydrodynamic model test results. To enhance data precision, this study presents an efficient calibration device based on a dual-axis rotational mechanism, enabling multi-degree-of-freedom attitude adjustment of the sensor. By applying known forces and moments through various loading conditions and employing the least squares method to obtain a 6 × 6 calibration coefficient matrix, we effectively reduce system errors and external disturbances. The effectiveness of the proposed calibration method is validated using rotational arm tests with a KCS standard ship model. The results indicate that most calibration point errors are below 1%, with the maximum error not exceeding 7%, and the measured data show good agreement with international standards. This method offers high calibration efficiency and accuracy, making it well-suited for the calibration of multi-component force sensors and for use in hydrodynamic, wind tunnel, and other multi-disciplinary experimental applications, promising potential for wider use.

Design of an Experimental Teaching Platform for Flow-Around Structures and AI-Driven Modeling in Marine Engineering - Hongyang Zhao; Bowen Zhao; Xu Liang; Qianbin Lin (Journal of Marine Science and Engineering, 2025)
Flow past bluff bodies (e.g., circular cylinders) forms a canonical context for teaching external flow separation, vortex shedding, and the coupling between surface pressure and hydrodynamic forces in offshore engineering. Conventional laboratory implementations, however, often fragment local and global measurements, delay data feedback, and omit intelligent modeling components, thereby limiting the development of higher-order cognitive skills and data literacy. We present a low-cost, modular, data-enabled instructional hydrodynamics platform that integrates a transparent recirculating water channel, multi-point synchronous circumferential pressure measurements, global force acquisition, and an artificial neural network (ANN) surrogate. Using feature vectors composed of Reynolds number, angle of attack, and submergence depth, we train a lightweight AI model for rapid prediction of drag and lift coefficients, closing a loop of measurement, prediction, deviation diagnosis, and feature refinement. In the subcritical Reynolds regime, the measured circumferential pressure distribution for a circular cylinder and the drag and lift coefficients for a rectangular cylinder agree with empirical correlations and published benchmarks. The ANN surrogate attains a mean absolute percentage error of approximately 4% for both drag and lift coefficients, indicating stable, physically interpretable performance under limited feature inputs. This platform will facilitate students’ cross-domain transfer spanning flow physics mechanisms, signal processing, feature engineering, and model evaluation, thereby enhancing inquiry-driven and critical analytical competencies. Key contributions include the following: (i) a synchronized local pressure and global force dataset architecture; (ii) embedding a physics-interpretable lightweight ANN surrogate in a foundational hydrodynamics experiment; and (iii) an error-tracking, iteration-oriented instructional workflow. The platform provides a replicable pathway for transitioning offshore hydrodynamics laboratories toward an integrated intelligence-plus-data literacy paradigm and establishes a foundation for future extensions to higher Reynolds numbers, multiple body geometries, and physics-constrained neural networks.

Microglia-derived extracellular vesicles mediate fine particulate matter-induced Alzheimer's disease-like behaviors through the miR-34a-5p/DUSP10/p-p38 MAPK pathway - Ling Wang; Yi Lin; Ziyi Yang; Ke Zhang; Hongyang Gong; Yaopeng Zheng; Binquan Wang; Xiaoyan Zhang; Mingkuan Sun (Journal of Hazardous Materials, 2025)

Synthesis and characterization of geopolymer microspheres at H3PO4 activated metakaolin and adsorption-immobilization performance of F− - Lin Shao; Hongyang Wei; Huiye Lei; Xingyong Xue; Liu He; Feng Gao; Kaituo Wang (Journal of Cleaner Production, 2025)

ε-MnO2 with oxygen defect Engineering: Modulating local electron density to enhance superoxide radical generation via peroxymonosulfate activation - Xiaoxi Guo; Zhuoyan Liu; Hongyang Wu; Chang Liu; Lin Shen; Ke Xu; Ji Wu; Yijun Cao (Journal of Cleaner Production, 2025)

Combining the life cycle model and corrosion model to analyze the impact of corrosion on carbon emissions of steel pipelines - An Yan; Ying Xiao; Hongyang Ren; Bing Lin; Hailong Zhang; Yingying Wang; Xi Li; Bing Wang; Junlei Tang (Environmental Impact Assessment Review, 2025)

Disentangling wavy and vortical motions in concurrent snapshots of the sea surface height and velocity - Chuanyin Wang; Zhiyu Liu; Hongyang Lin; Cesar Rocha; Qinghua Yang; Dake Chen; Junbin Gong (Ocean Modelling, 2025)

Targeting 5-HT to Alleviate Dose-Limiting Neurotoxicity in Nab-Paclitaxel-Based Chemotherapy - Shuangyue Pan; Yu Cai; Ronghui Liu; Shuting Jiang; Hongyang Zhao; Jiahong Jiang; Zhen Lin; Qian Liu; Hongrui Lu; Shuhui Liang; Weijiao Fan; Xiaochen Chen; et al. (Neuroscience Bulletin, 2025)

Pilot-scale application on Fe-C coupled natural zeolite for total nitrogen removal in low C/N black odorous water - Hongyang Yu; Qiheng Han; Tao Li; Shanshan Lin (Journal of Environmental Chemical Engineering, 2025)

Efficiency of iron–carbon microelectrolysis in the treatment of nitrate and phosphate in printed circuit board production wastewater: The critical role of Cu2+ - Hongyang Yu; Xinlong Wang; Xiangru Liu; Dongyu Peng; Huina Liu; Xin Yang; Shanshan Lin (Journal of Environmental Chemical Engineering, 2025)

Carbon Utilization and Denitrification Intermediates Adjustment Strategies: Improved Biopolymer Polyhydroxybutyrate Production and Reuse by Electrode Potential Regulation - Feng Lin; Xin Li; Xuyan Zhu; Qi Sun; Yongze Lu; Guangcan Zhu; Hongyang Wang (Chemical Engineering Journal, 2025)

The reflux of water transport in the intermediate layer of Luzon Strait - Ziyun Yang; Wei Zhuang; Hongyang Lin; Jianyu Hu (Ocean Dynamics, 2025)

A large-scale FireLine global positioning method based on a single unmanned aerial vehicle - Yifan Fu; Haiyu Zhang; Xingdong Li; Chuanying Lin; Yue Ma; Hongyang Zhao; Shufa Sun (International Journal of Remote Sensing, 2025)

Phosphine oxide functionalized porous aromatic frameworks enabled wireless bionic olfactory system with preconcentration capability for trace ammonia monitoring - Shuai Zhao; Hongyang Jin; Zihao Chen; Yonglai Zhang; Xiaoqin Zou; Lin Xu; Shaolei Wang; Zhenglei Yu; Zhiyong Chang (Chemical Engineering Journal, 2025)

Enhancement of the reactivation process of long-term starved anammox granular sludge with gravel balls: Microbial succession and metabolic impact - Xinlong Wang; Qiheng Han; Hongyang Yu; Shanshan Lin (Environmental Research, 2024)

Recombinant avian-derived antiviral proteins cIFITM1, cIFITM3, and cViperin as effective adjuvants in inactivated H9N2 subtype avian influenza vaccines - Shihong Yan; Yikai Chen; Jin Lin; Huimin Chen; Chenqi Hu; Hongyang Liu; Hongxiu Diao; Shasha Liu; Ji-Long Chen (Veterinary Microbiology, 2024)

Is cognition of residential tiered pricing policy effective in reducing electricity consumption in China? - Hongyang Lin; Huanyu Jia; Yingjin Ye; Yu Shen; Boqiang Lin (Utilities Policy, 2024)

Synergistic selenium doping and colloidal quantum dots decoration over ZnIn2S4 enabling high-efficiency photoelectrochemical hydrogen peroxide production - Hongyang Zhao; Yisen Yao; Mengke Cai; Xin Li; Peihang Li; Ali Imran Channa; Feng Lin; Mingzhu Wang; Zhiming M. Wang; Xin Tong (Chemical Engineering Journal, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

CNT-based water-induced generator for effective self-powered devices via superior synergism between electrokinetic and galvanic effects - Linan Xu; Wenxing Wang; Xiaoguang Li; Hongjian Yu; Xinyuan Liu; Yang Zhang; Hongyang Xu; Song Lin; Xing Yi Ling; Haitao Li (Chemical Engineering Journal, 2023)

Removal of Nitrate from Wastewater by Nanoscale Zero-Valent Iron Synthesized from Polyhydroxy Alcohols - Huina Liu; Hongyang Yu; Yifeng Wu; Dongyu Peng; Shanshan Lin (Water, Air, & Soil Pollution, 2023)

Potential determinants affecting the growth of China’s ocean economy: An input-output structural decomposition analysis - Li Zheng; Hongyang Zou; Xiaofeng Duan; Zhongguo Lin; Huibin Du (Marine Policy, 2023)

Development of an atmosphere temperature measurement system based on computational fluid dynamics and neural network algorithms - Hongyang Guo; Jie Yang; Huanan Zhu; Zitao Lin; Yuhan Yun (Building and Environment, 2023)

Continuous rotating bending NiTi sheets for elastocaloric cooling: Model and experiments - Siyuan Cheng; Yinan Xiao; Xueshi Li; Hongyang Lin; Peng Hua; Liyuan Sheng (International Journal of Refrigeration, 2023)

DOK7 Promotes NMJ Regeneration After Nerve Injury - Ethan D. Kosco; Hongyang Jing; Peng Chen; Wen-Cheng Xiong; Ivy S. Samuels; Lin Mei (Molecular Neurobiology, 2023)

AIFM1 variants associated with auditory neuropathy spectrum disorder cause apoptosis due to impaired apoptosis-inducing factor dimerization - Yue Qiu; Hongyang Wang; Huaye Pan; Jing Guan; Lei Yan; Mingjie Fan; Hui Zhou; Xuanhao Zhou; Kaiwen Wu; Zexiao Jia; Qianqian Zhuang; Zhaoying Lei; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Efficient preparation of red mud-based geopolymer microspheres (RM@GMs) and adsorption of fluoride ions in wastewater - Min Yi; Kaituo Wang; Hongyang Wei; Deshuai Wei; Xuefei Wei; Binghu Wei; Lin Shao; Toyohisa Fujita; Xuemin Cui (Journal of Hazardous Materials, 2023)

Manganese-modified biochar promotes Cd accumulation in Sedum alfredii in an intercropping system - Xuejiao Chen; Qimei Lin; Hongyang Xiao; Rizwan Muhammad (Environmental Pollution, 2023)

Lagrangian Observation of the Kuroshio Current by Surface Drifters in 2019 - Zhenyu Sun; Jianyu Hu; Hongyang Lin; Zhaozhang Chen; Jia Zhu; Longqi Yang; Zhiyuan Hu; Xirong Chen; Xuewen Wu (Journal of Marine Science and Engineering, 2022)
In this research, the features of the Kuroshio Current in 2019 were studied based on the observations of 29 self-developed surface current experiment drifters deployed in the western Pacific Ocean and the East China Sea. The Kuroshio flow pattern and velocity magnitude observed in 2019 were largely consistent with the climatology based on the historical drifter dataset, but they still exhibited distinctive characteristics. The intrusion of the Kuroshio into the South China Sea in the spring was observed by a group of drifters crossing the Luzon Strait from east to west, which is a notable departure from the non-intrusion pattern noted to occur in the spring in most of the historical records. A strong intrusion of the Kuroshio into the East China Sea was also observed, taking an anti-cyclonic turn in the northeast of Taiwan Island. Both the drifter trajectories and altimeter-derived dynamical topography captured the large meander pattern of the Kuroshio south of Japan in 2019, with the flow path having a maximum offshore distance of 470 km. In addition, Lagrangian statistics (lateral diffusivity, integral time scale, and integral space scale) were estimated for four selected regions with adequate drifter samplings. The lateral diffusivity had large values along the Kuroshio segment in the East China Sea and small values on the continental shelf of the East China Sea. The integral time scales for the four regions ranged from 0.8 to 3.7 days, with a corresponding integral space scale of 19~128 km.

Deficiency of Klc2 Induces Low-Frequency Sensorineural Hearing Loss in C57BL/6 J Mice and Human - Xiaolong Fu; Yachun An; Hongyang Wang; Peipei Li; Jing Lin; Jia Yuan; Rongyu Yue; Yecheng Jin; Jiangang Gao; Renjie Chai (Molecular Neurobiology, 2021)

Regional differences of air pollution in China: comparison of clustering analysis and systematic clustering methods of panel data based on gray relational analysis - Huangxin Chen; Lin Zhang; Wenjie Zou; Qi Gao; Hongyang Zhao (Air Quality, Atmosphere & Health, 2020)

Immobilization of Lead and Cadmium in Soil Using Biochars Derived from Pig Manure and Suaeda glauca - Yarui Liu; Fei Wang; Zheyun Yin; Weili Jia; Hongyang Xiao; Qimei Lin; Yujie Feng (Bulletin of Environmental Contamination and Toxicology, 2020)

Surface currents measured by GPS drifters in Daya Bay and along the eastern Guangdong coast - Yang Gao; Yongxiang Huang; Hongyang Lin; Zhenyu Sun; Jia Zhu; Jianyu Hu (Frontiers of Earth Science, 2020)

Wintertime Guangdong coastal currents successfully captured by cheap GPS drifters - Hongyang Lin; Zhenyu Sun; Zhaozhang Chen; Jia Zhu; Jianyu Hu (Acta Oceanologica Sinica, 2020)

Analysis of temperature inversion in the Zhujiang River Estuary in July 2015 - Xirong Chen; Zhenyu Sun; Hongyang Lin; Jia Zhu; Jianyu Hu (Acta Oceanologica Sinica, 2019)

Classification and 3-D distribution of upper layer water masses in the northern South China Sea - Jia Zhu; Quanan Zheng; Jianyu Hu; Hongyang Lin; Dewen Chen; Zhaozhang Chen; Zhenyu Sun; Liyan Li; Hao Kong (Acta Oceanologica Sinica, 2019)

Tide- and wind-driven variability of water level in Sansha Bay, Fujian, China - Hongyang Lin; Jianyu Hu; Jia Zhu; Peng Cheng; Zhaozhang Chen; Zhenyu Sun; Dewen Chen (Frontiers of Earth Science, 2017)

Development of a core set of single-locus SSR markers for allotetraploid rapeseed (Brassica napus L.) - Haitao Li; Muhammad Younas; Xiaofeng Wang; Xuemin Li; Lin Chen; Bo Zhao; Xun Chen; Jinsong Xu; Fan Hou; Baohua Hong; Gang Liu; Hongyang Zhao; et al. (Theoretical and Applied Genetics, 2013)

Satellite altimeter observations of nonlinear Rossby eddy–Kuroshio interaction at the Luzon Strait - Quanan Zheng; Chang-Kuo Tai; Jianyu Hu; Hongyang Lin; Rong-Hua Zhang; Feng-Chun Su; Xiaofeng Yang (Journal of Oceanography, 2011)